1989
DOI: 10.1073/pnas.86.13.5044
|View full text |Cite
|
Sign up to set email alerts
|

Short, direct repeats at the breakpoints of deletions of the retinoblastoma gene.

Abstract: We found deletions involving the retinoblastoma gene in 12 of49 tumors from patients with retinoblastoma or osteosarcoma. After mapping the deletion breakpoints, we found that no two breakpoints coincided. Thus, our data do not support the conclusions of others regarding the existence of a "hotspot" for deletion breakpoints in this gene. In 4 of the tumors, we sequenced 200 base pairs surrounding each deletion breakpoint. Three deletions had termini within pairs of short, direct repeats ranging in size from 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 43 publications
2
57
0
Order By: Relevance
“…Several studies on the mechanism of deletions have shown that -40% of the large deletions in human disorders are Hanked by very short direct repeats of 2-6 bp (37)(38)(39). It is proposed that these short repeats slip and mispair during replication, resulting in the formation of a loop between the two repeats (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on the mechanism of deletions have shown that -40% of the large deletions in human disorders are Hanked by very short direct repeats of 2-6 bp (37)(38)(39). It is proposed that these short repeats slip and mispair during replication, resulting in the formation of a loop between the two repeats (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that these short repeats slip and mispair during replication, resulting in the formation of a loop between the two repeats (37,38). Subsequent excision of this loop removes both the sequences between the repeats as well as one of the repeats.…”
Section: Discussionmentioning
confidence: 99%
“…(Cowell, 1992). All three mutations reported here are in different exons which contributes to the emerging pattern that no particular part of the gene is preferentially involved in mutation (Canning & Dryja, 1989;Dunn et al, 1989;). (1985) concluded that short direct repeats, of at least 2 bp, occurred more frequently than would be expected from random breakage and reunion.…”
Section: Mechanisms Of Mutationmentioning
confidence: 65%
“…Notably, microhomology sequences suggestive of ALT-NHEJ have been found at the recombination junctions of radiation-induced genomic rearrangements (Morris andThacker, 1993, Nohmi et al, 1999) implying that radiation-induced DSBs can be repaired by ALT-NHEJ. Moreover, microhomologies are frequently detected at the breakpoints of chromosomal deletions and translocations in human cancer cells (Canning and Dryja, 1989, Smanik et al, 1995, Wiemels and Greaves, 1999.…”
Section: Microhomologiesmentioning
confidence: 99%
“…They mapped the deletion breakpoints and sequenced 200 base pairs surrounding each deletion breakpoint in DNA from 4 tumor samples. Three deletions had termini characterized by direct repeats ranging in size from 4 to 7 base pairs (Canning and Dryja, 1989). Recurrent chromosome translocations characterize leukemia and lymphoma and are specifically associated with their classification and prognosis.…”
Section: Microhomologies At Breakpoints Junction Of Recurrent Alteratmentioning
confidence: 99%